2020
DOI: 10.1002/lom3.10381
|View full text |Cite
|
Sign up to set email alerts
|

Application of purge and trap‐atmospheric pressure chemical ionization‐tandem mass spectrometry for the determination of dimethyl sulfide in seawater

Abstract: We describe a method for measuring trace concentrations of dimethyl sulfide (DMS) in seawater using a commercial tandem mass spectrometer configured for atmospheric pressure chemical ionization (PT-APCI-MS/MS), coupled with a custom-built purge and trap gas extraction system. DMS was ionized through proton transfer, generating abundant [M + H] + ions. The semiautomated method analyzes samples in under 6 min, and is capable of processing up to 10 samples in a single batch. A detection limit of 0.9 pmol L −1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…For the analysis of 10 consecutive samples, the coefficient of variation between sequential DMS signals was 5.4% by peak area and 5.5% by peak height. This level of precision is consistent with the reproducibility provided by the P&T‐APCI‐MS/MS method used for DMS analysis (3.9% by peak area and 4.1% by peak height; McCulloch et al 2020), indicating that the introduction of the electrochemical reduction method does not substantially impact the reproducibility of the overall analysis. The level of reproducibility provided is also consistent with other purge and trap GC‐based DMS detection techniques (Kiene 1996; Zindler et al 2012; Zhang and Chen 2015).…”
Section: Methodssupporting
confidence: 80%
See 3 more Smart Citations
“…For the analysis of 10 consecutive samples, the coefficient of variation between sequential DMS signals was 5.4% by peak area and 5.5% by peak height. This level of precision is consistent with the reproducibility provided by the P&T‐APCI‐MS/MS method used for DMS analysis (3.9% by peak area and 4.1% by peak height; McCulloch et al 2020), indicating that the introduction of the electrochemical reduction method does not substantially impact the reproducibility of the overall analysis. The level of reproducibility provided is also consistent with other purge and trap GC‐based DMS detection techniques (Kiene 1996; Zindler et al 2012; Zhang and Chen 2015).…”
Section: Methodssupporting
confidence: 80%
“…This study demonstrates the performance and practicality of a new electrochemically driven reduction protocol, which facilitates the accurate, selective, and reproducible measurement of DMSO in aqueous solutions. When coupled with the P&T-APCI-MS/MS workflow described previously (McCulloch et al 2020), the method can detect DMSO at concentrations typically observed within both fresh and seawater samples. The new electrochemical reduction method represents an alternative to existing enzyme-linked and reagent-based chemical reduction methods for DMSO analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over a period of ~ 2–5 h, we collected 5 mL subsamples from each sample bag every 30–90 min using a glass syringe with a Luer Lock port. The concentration of isotopically labeled DMS species was determined using a SCIEX API 3200‐series triple quadrupole mass spectrometer equipped with an atmospheric pressure chemical ionization source (McCulloch et al, 2020). DMS, and each of its isotopically labeled analogues were found to ionize exclusively through the proton transfer (PT) mechanism, yielding abundant [M+H] + ions.…”
Section: Methodsmentioning
confidence: 99%